A STUDY OF DESTINATION ATTRACTIVENESS TOWARD MANADO AS TOURIST DESTINATION - Durian, Rivicky P.; Kindangen, Paulus; Arie, Fitty Valdi (Universitas Sam Ratulangi, 2021)
In the last two decades, tourism activities have grown rapidly to become one of the mainstays in the economic field. The most popular destination is Bunaken National Park which is believed to be one of the most beautiful marine parks in the world. This study aims to analyze the attractiveness of Manado as a tourism destination. The reason the researcher chooses this topic is because not much research on tourism has been done in recent years, including Manado. This study uses a descriptive qualitative methodology and takes seven informants who are tourists in the city of Manado and have visited Manado more than twice, both locally and internationally. Researchers conclude that attraction is a force that attracts tourists. Based on the analysis, the conclusions given in this study are Cultural Sites in Manado are the main attraction for tourists to visit Manado, access to places visited in Manado needs to be maintained so as not to lose their value, Facilities for tourists in Manado are sufficient and need to be maintained , The local community has done well in its part which will attract tourists to stay in Manado.Â Keyword: destination attractiveness, local community